PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN E-COMMERCE SOCIOLLA - Faradilah Meida (2021)
This study aims to analyze and prove whether there is an influence between service quality and trust on customer satisfaction. This research method is quantitative and the sample of Sociolla E-commerce consumers spread in DKI Jakarta province is 100 respondents. The data analysis technique used descriptive analysis and inferential analysis using SmartPLS analysis. The results showed that service quality affected customer satisfaction. Trust does not affect customer satisfaction. And together the variables of service quality and trust influence customer satisfaction.